Companion Crops for Organic Alfalfa Establishment. (1st January 2014) - Sheaffer, Craig C.; Martinson, Krishona M.; Wyse, Donald L.; Moncada, Kristine M.
Abstract : In organic cropping systems, companion crops are used for establishment of forage legumes, but a comparison of alternative companion crops for alfalfa ( Medicago sativa L.) has not been conducted. We determined the yield of spring‐seeded companion crops and their effect on alfalfa forage yield, weed yield, and net return in five environments. Crops were managed using organic practices. Barley ( Hordeum vulgare L.) was among the highest yielding small grains, while annual ryegrass ( Lolium multiflorium Lam.) was among the highest yielding forage companion crops. Companion crop effects on alfalfa yields were inconsistent among environments. In the establishment year, in two environments, alfalfa yields were similar for all establishment treatments. In three environments, rapid cycling brassica ( Brassica rapa L.), annual ryegrass, and winter wheat ( Triticum aestivum L.) companion crop treatments often resulted in alfalfa yields that were greater than those following field pea ( Pisum sativum L.), flax ( Linum usitatissimum L.), barley, oat ( Avena sativa L.), and wheat. In the year following seeding, alfalfa yields in three environments were similar for all treatments, while in two environments, all treatments except field pea had yields equal to a weedy control. Spring‐seeded wheat, barley, and oat companion crops provided greater net returns than the control, field pea, flax, or forage (non‐vernalized winter wheat, annual ryegrass, and rapid‐cycling brassica) companion crop treatments. Small grain companion crops provide high and consistent net returns without adversely affecting alfalfa yields, and should be used for alfalfa establishment in organic crop production systems.